Exchange hazards, relational reliability, and contracts in China: The contingent role of legal enforceability - Zhou, Kevin Zheng; Poppo, Laura (Journal of international business studies, 2010)
Building on institutional and transaction cost economics, this article proposes that legal enforceability increases the use of contract over relational reliability (e.g., beliefs that the other party acts in a non-opportunistic manner) to safeguard market exchanges characterized by non-trivial hazards. The results of 399 buyer-supplier exchanges in China show that: (1) when managers perceive that the legal system can protect their firm's interests, they tend to use explicit contracts rather than relational reliability to safeguard transactions involving risks (i.e., asset specificity, environmental uncertainty, and behavioral uncertainty); and (2) when managers do not perceive the legal system as credible, they are less likely to use contracts, and instead rely on relational reliability to safeguard transactions associated with specialized assets and environmental uncertainty, but not those involving behavioral uncertainty. We further find that legal enforceability does not moderate the effect of relational reliability on contracts, but does weaken the effect of contracts on relational reliability. These results endorse the importance of prior experience (e.g., relational reliability) in supporting the use of explicit contracts, and alternatively suggest that, under conditions of greater legal enforceability, the contract signals less regarding one's intention to be trustworthy but more about the efficacy of sanctions.